Iodine-mediated cyclization of cannabigerol (CBG) expands the cannabinoid biological and chemical space. Issue 15 (15th August 2018) - Lopatriello, Annalisa; Caprioglio, Diego; Minassi, Alberto; Schiano Moriello, Aniello; Formisano, Carmen; De Petrocellis, Luciano; Appendino, Giovanni; Taglialatela-Scafati, Orazio
Graphical abstract: Abstract: Electrophilic attack to a double bond, the classic trigger of intramolecular isoprenoid cyclizations, is apparently silent in Cannabis and the diversity of the cannabinome can be ultimately traced to the oxidative cyclization of cannabigerolic acid (CBGA, 1a ), a process triggered by the generation of an aromatic electrophilic species. To expand the chemical space of the cannabinoid chemotype, we have investigated an oxidative trigger based on the addition of iodine to the terminal isoprenyl double bond of cannabigerol (CBG, 1b ), the decarboxylated and thermally stable version of CBGA (1a ). Apart from the predictable product of an iodine-induced cascade cyclization (3 ), also a pair of unprecedented spiranes named spirocannabigerols (4a, b ), derived from the formation of an edge-protonated cyclopropyl cation was also formed, along with a product (5 ) resulting from the incorporation, in a Friedel-Craft fashion, of the reaction solvent (toluene). Biological evaluation of these compounds on six thermo-transient receptor potential channels (TRPs) showed a remodeling of bioactivity compared to GBC, with emphasis on TRPA1 rather than TRPM8.